Service Marketing Mix Influencing the Purchase Decision for a Community Agricultural Product, The Doi Kham Brand - Chienwattanasook, Krisada; Palagawong na Ayutaya, Papatcha; Tubtimnak, Soontaree; Soonthonrot, Pakaphon (Journal of Management Science Nakhon Pathom Rajabhat University, 2024)
The objective of this research is to test the service marketing mix factors (7Ps) that influence the decision to purchase Doi Kham brand community agricultural products. The data for this study was collected using electronic questionnaires to collect a sample of people who had previously purchased Doi Kham brand community agricultural products, selected through online social networks, and obtained a complete sample of 344 people. Statistical analyzes used in the data analysis included frequency, percentage, mean, standard deviation, and hypothesis testing using a Partial Least Square Structural Equation Model (PLS-SEM). The results of this study show that the service marketing mix (7Ps), including price, distribution channels, promotion, and physical evidence, significantly influence the purchase decisions of community agricultural products of Doi Kham brand and have statistically significant effects at the .001, .027, .000, and .000 levels, respectively. The research results will be useful for entrepreneurs to know the influence on consumers’ purchase decisions for community agricultural products, and they will be able to use the research results as recommendations to improve and develop product and service management to achieve effective integration with customers. Article history: Received 15 May2023 Revised 6 December 2023 Accepted 8 December 2023 SIMILARITY INDEX = 6.10%